Using Renewable-Based Microgrid Capabilities for Power System Restoration - João Pedro Pereira Carvalho (2018)
Power system restoration (PSR) is a very important procedure to ensure the consumer supply. In this paper, a decentralized multi-agent system (MAS) for dealing with the microgrid restoration procedure is proposed. In this proposed method, each agent is associated to a consumer or microsource (MS) and these will communicate between each other in order to reach a common decision. The agents solve a 0/1 knapsack problem to determine the best load connection sequence during the microgrid restoration procedure. The proposed MAS is tested in two different case studies: a total blackout and a partial blackout, in which the emergency demand response programs are considered. It is developed in the Matlab/Simulink environment and is validated by performing the corresponding dynamic simulations.